‘The age of school shootings’: A sociological interpretation on masculinity / ‘La era de las masacres en las escuelas’: Una interpretación sociológica sobre la masculinidad - Celis, Jorge (2015)
Over the past two decades there has been a growing interest in the study of the horrendous massacres perpetrated by students at school premises. These massacres, known as school shootings, haven been predominantly analyzed by employing psychological approaches. Despite the fact that empirical research clearly reveals that school shooters tend not to present life-long histories of mental illness, these approaches usually put a strong emphasis on the perpetrator’s individual pathologies, ignoring the influence that social values such as masculinity exert on perpetrators’ actions. Consequently, perpetrators are viewed as lone wolf shooters and school shootings as isolated cases. Based on data derived from scholarly works published mainly in peer-review journals and the sociological theory of P. Berger and T. Luckmann, the aim of this essay is to offer a sociological interpretation on school shootings by explaining why school shooters commit violent actions against teachers and classmates as a form of retrieving their masculinity. In this regard, the essay finds that male rather than female students commit school shootings. At the same time, the majority of perpetrators have had parents who were gun collectors. It is no coincide that shooters mostly use family guns to commit the massacres. Additionally, shooters see school as a social entity that has diminished their masculinity, and the way to reaffirm their masculinity is to attack randomly students and teachers in full view of the rest of school members during school hours.  En las dos últimas décadas se ha presentado un interés creciente por el estudio de las horrendas masacres cometidas por estudiantes en las escuelas. Estas masacres conocidas como “tiroteos en la escuela” han sido analizadas utilizando enfoques psicológicos. A pesar de que la investigación revela que los perpetrados no presentan historias de enfermedades mentales, estos enfoques enfatizan en las patologías de los perpetrados ignorando la influencia que los valores tienen sobre sus acciones. En consecuencia, los perpetradores son vistos como lobos solitarios y las masacres escolares como casos aislados. Con base en información obtenida de trabajos académicos publicados, en su gran mayoría, en revistas científicas, y además, con la teoría sociológica de P. Berger y T. Luckmann, el propósito de este ensayo es presentar una interpretación sociológica sobre las masacres ocurridas en las escuelas al explicar por qué los perpetradores cometen actos violentos contra sus profesores y compañeros como una forma de recuperar su masculinidad. El ensayo encuentra que los hombres más que las mujeres cometen tiroteos en las escuelas. Por lo general, los perpetrados provienen de padres quienes han sido coleccionistas de armas. No es coincidencia que los perpetrados utilicen las armas de sus familias para llevar a cabo las masacres. Aunado a ello, los perpetrados perciben la escuela como una entidad social que disminuye su masculinidad, y la manera de reafirmarla es mediante el ataque azaroso a estudiantes y profesores en frente del resto de los miembros de la comunidad educativa durante la jornada escolar.